Sprint, agility, strength and endurance capacity in wheelchair basketball players - Yanci, Javier; Granados, Cristina; Otero, Montserrat; Badiola, Aduna; Olasagasti, Jurgi; Bidaurrazaga-Letona, Iraia; Iturricastillo, Aitor; Gil, Susana M (Biology of Sport, 2015)
The aims of the present study were, firstly, to determine the reliability and reproducibility of an agility T-test and Yo-Yo 10 m recovery test; and secondly, to analyse the physical characteristics measured by sprint, agility, strength and endurance field tests in wheelchair basketball (WB) players. 16 WB players (33.06 ± 7.36 years, 71.89 ± 21.71 kg and sitting body height 86.07 ± 6.82 cm) belonging to the national WB league participated in this study. Wheelchair sprint (5 and 20 m without ball, and 5 and 20 m with ball) agility (T-test and pick-up test) strength (handgrip and maximal pass) and endurance (Yo-Yo 10 m recovery test) were performed. T-test and Yo-Yo 10 m recovery test showed good reproducibility values (intraclass correlation coefficient, ICC = 0.74-0.94). The WB players’ results in 5 and 20 m sprints without a ball were 1.87 ± 0.21 s and 5.70 ± 0.43 s and with a ball 2.10 ± 0.30 s and 6.59 ± 0.61 s, being better than those reported in the literature. Regarding the pick-up test results (16.05 ± 0.52 s) and maximal pass (8.39 ± 1.77 m), players showed worse values than those obtained in elite players. The main contribution of the present study is the characterization of the physical performance profile of WB players using a field test battery. Furthermore, we demonstrated that the agility T-test and the aerobic Yo-Yo 10 m recovery test are reliable; consequently they may be appropriate instruments for measuring physical fitness in WB.